2024
DOI: 10.1111/1753-0407.13533
|View full text |Cite
|
Sign up to set email alerts
|

Financial conflicts of interest among authors of clinical practice guidelines for diabetes mellitus in Japan

Anju Murayama

Abstract: Clinical practice guidelines (CPGs) serve as pivotal frameworks for standardizing evidence-based diagnostic and therapeutic approaches, particularly in the management of diabetes and beyond. 1,2 However, the integrity of these guidelines can be compromised by conflicts of interest (COIs). [3][4][5] Given that current increasing attention from pharmaceutical companies to diabetologists 6,7 and large prevalence of diabetes and obesity, proper management of financial COIs is essential for trustworthy diabetes CPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The high prevalence (77.2%) of financial ties to drug companies for non-research purposes among the authors in this study aligns with many previous studies in Japan, albeit with higher percentages. [3][4][5][6][7][8][9]13,41,42,[44][45][46][47][48] This could indicate a vulnerability to financial COI among the influential breast cancer experts in Japan. For example, the author previously reported that the proportions of authors accepting payments from drug companies were 66.0% in obstetrics and gynecology, 13 88% in nephrology, 5 88.2% in gastroenterology, 3,45 88.6% in urology, 46 90.6% in dermatology, 47 91.3%-100% in rheumatology, 4,41 87.0%-91.9% in infectious diseases, 6,44 94.4% in cardiology, 48 94.6% in hematology, 9 95.6% in a diabetes CPG, 42 96.3% in otolaryngology 7 and 100% in a CPG for hepatitis C treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence (77.2%) of financial ties to drug companies for non-research purposes among the authors in this study aligns with many previous studies in Japan, albeit with higher percentages. [3][4][5][6][7][8][9]13,41,42,[44][45][46][47][48] This could indicate a vulnerability to financial COI among the influential breast cancer experts in Japan. For example, the author previously reported that the proportions of authors accepting payments from drug companies were 66.0% in obstetrics and gynecology, 13 88% in nephrology, 5 88.2% in gastroenterology, 3,45 88.6% in urology, 46 90.6% in dermatology, 47 91.3%-100% in rheumatology, 4,41 87.0%-91.9% in infectious diseases, 6,44 94.4% in cardiology, 48 94.6% in hematology, 9 95.6% in a diabetes CPG, 42 96.3% in otolaryngology 7 and 100% in a CPG for hepatitis C treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9]13,41,42,[44][45][46][47][48] This could indicate a vulnerability to financial COI among the influential breast cancer experts in Japan. For example, the author previously reported that the proportions of authors accepting payments from drug companies were 66.0% in obstetrics and gynecology, 13 88% in nephrology, 5 88.2% in gastroenterology, 3,45 88.6% in urology, 46 90.6% in dermatology, 47 91.3%-100% in rheumatology, 4,41 87.0%-91.9% in infectious diseases, 6,44 94.4% in cardiology, 48 94.6% in hematology, 9 95.6% in a diabetes CPG, 42 96.3% in otolaryngology 7 and 100% in a CPG for hepatitis C treatment. 8 Meanwhile, previous studies in other high-income countries, such as the United States, the UK and Canada, reported lower fraction of COIs for CPG authors than TA B L E 4 New approval and indications of breast cancer drugs manufactured by the top five companies making the largest payments in Japan between 2010 and 2022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies indicated significant undeclared and under-reported COIs between physicians and pharmaceutical companies in Japan. 2025 27 31 45 49 Our previous study elucidated that more than 94% of authors of clinical practice guidelines for cardiovascular diseases received personal payments from pharmaceutical companies in Japan. 45 Additionally, the policies used to manage COIs in Japan are less rigorous and transparent than those in other high-income countries.…”
Section: Discussionmentioning
confidence: 99%